A “Fork-to-Farm” Multi-Scale Approach to Promote Sustainable Food Systems for Nutrition and Health: A Perspective for the Mediterranean Region - Verger, Eric O.; Perignon, Marlene; El Ati, Jalila; Darmon, Nicole; Dop, Marie-Claude; Drogué, Sophie; Dury, Sandrine; Gaillard, Cédric; Sinfort, Carole; Amiot, Marie-Josèphe; , MEDINA-Study Group; Amiot, Marie-Josèphe; et al. (Frontiers in Nutrition, 2018)
Mediterranean countries are undergoing dietary and nutritional changes that affect their inhabitants’ health, while facing massive environmental challenges. The increasing demand of water in agriculture, the capacity to maintain local food production, and the growing dependence on food imports are interconnected issues that must be addressed to ensure food security and nutrition in the Mediterranean region. Here, we present the conceptual framework and methodologies developed by the MEDINA-Study Group for rethinking food systems towards sustainable consumption and production modes. Based on its multidisciplinary expertise, the MEDINA-Study Group designed a “fork-to-farm” multi-scale approach, stemming from current dietary habits and examining how some options to nutritionally improve these habits might affect the food systems. This approach was developed for research activities in the South of France and Tunisia, two areas with very different diet-agriculture-environment nexus. The conceptual framework is based on the analysis of elements of the food systems (from consumption to production) at different levels (individual, household, regional and national levels). The methods include: i) modeling options of dietary changes at different scales, in order to nutritionally optimize food consumption-production without increasing the environmental impact, ii) translating the best-choice changes into possible policy actions, iii) testing the acceptability and feasibility of these actions with several stakeholders, and iv) producing guidelines for sustainable food choices and production. The MEDINA-Study Group identified additional issues that could be included in a future framework to help designing ambitious agricultural, food and health policies in the Mediterranean region.